#65 Respiratory Syncytial Virus Surveillance Among Hospitalized Children in Amman, Jordan. (14th June 2022) - Yanis, Ahmad
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of acute respiratory infection (ARI) in young children worldwide. In Jordan, RSV has previously been reported as the most frequently detected virus among hospitalized children less than two years. We aimed to compare the demographic and clinical characteristics of RSV-positive and RSV-negative hospitalized children during the peak season in Amman, Jordan. Method: Children under two years who presented with fever and/or respiratory symptoms within 72 hours of hospitalization at a government-run hospital were enrolled. We systematically collected demographic and clinical characteristics via parental interviews and medical chart abstractions. Anterior nasal and/or throat swabs were collected and tested for RSV by PCR. Differences in clinical characteristics were evaluated by RSV status using two-sample t- tests allowing for unequal variances for continuous variables and Pearson's Chi-squared test for categorical variables, alpha=0.05. Results: From January 8 to March 17, 2020, 531 children were enrolled and tested, of which 57% were male and had a mean age of 5 months. Of those who were tested, 401 (76%) were RSV-positive. Children with RSV were younger and less likely to have an underlying medical condition compared to children without RSV (Table 1). RSV-positive children were more likely to present with cough, shortness of breath, runny nose, nasal congestion, decreased appetite, vomiting, wheezing, and had a higher respiratory rate at admission than RSV-negative children. Compared to RSV-negative children, RSV-positive children were more likely to have an admission diagnosis of pneumonia and bronchiolitis and less likely have the diagnosis of rule out sepsis. Conclusion: In our study, more than three-quarters of children hospitalized with ARI had RSV. Additional prevention measures, such as vaccines or antivirals, are needed to effectively reduce the RSV burden among young children in Jordan.